Colonization by Staphylococcus aureus among the nursing staff of a teaching hospital in Pernambuco - Silva, Eduardo Caetano Brandão Ferreira da; Samico, Thammy Moura; Cardoso, Rodrigo Rosa; Rabelo, Marcelle Aquino; Bezerra Neto, Armando Monteiro; Melo, Fábio Lopes de; Lopes, Ana Catarina de Souza; Aca, Ivanize da Silva; Maciel, Maria Amélia Vieira (Revista da Escola de Enfermagem da USP, 2012)
This study was performed with the objective to identify the prevalence of colonization by Staphylococcus aureus in nursing professionals from a teaching hospital in Pernambuco, and evaluate the resistance profile of these isolates. To do this, we performed a cross-sectional study where biological samples were collected from the hands and nasal cavities of the subjects. S. aureus was identified using agar (blood agar and mannitol salt) via catalase and coagulase tests. The sensitivity profile was determined by Kirby Bauer technique and determination of methicillin resistance was performed with oxacillin screening with sodium chloride (NaCl) addition. Of the 151 professionals evaluated, 39 were colonized which showed a prevalence of 25.8%. Among the variables studied, age and use of PPE were associated with colonization by the organism. Of all the isolates, only five were resistant to methicillin.